A lower body height and wider foot stance are positively associated with the generation of individual scrummaging forces in rugby. (4th March 2017) - Green, Andrew; Kerr, Samantha; Dafkin, Chloe; Olivier, Benita; McKinon, Warrick
Abstract: A scrum is a contest to win possession of the rugby ball. The current study investigated potential kinematic parameters related to individual scrummaging force production. Twenty-five "tight-five" players (body mass: 103.0 ± 12.1 kg; height: 1.85 ± .09 m) individually scrummaged against an instrumented ergometer, while body kinematics were captured. Pearson's correlations between force generation and kinematics of individual scrummaging performances were performed. Body mass was correlated to the engagement ( r  = .641), peak ( r  = .531) and sustained ( r  = .438) forces. Stance width was significantly correlated with the individual scrummaging forces at engagement ( r  = .422) and sustained phases ( r  = .540) but not at peak phase ( r  = .369). Higher scrummaging forces were achieved at lower pelvic and back heights. The only significant relationship during the start-sustained phase was the change in pelvic height ( r  = −.562). Changes in right hip ( r  = −.477) and right knee ( r  = .474) angles were correlated to the change in force during engagement-peak phase. During engagement-sustained phases, change in force magnitude was correlated to changes in pelvic height ( r  = −.585), left hip ( r  = .549) and right ankle ( r  = .657). The change in pelvic height ( r  = −.518) was the only correlate during the peak-sustained phase. The presented data highlight the role of a lower body height and wider stance in the attainment of greater individual scrummaging force.